PENGARUH TINGKAT PENDIDIKAN DAN PEMAHAMAN MASYARAKAT TENTANG IKAN BERFORMALIN TERHADAP KESEHATAN MASYARAKAT - SRIYONO SRIYONO (LPPM, 2015)
Although formalin is not a food preservative but is still widely used by the public. This is because the level of knowledge and understanding is still lacking. These scientific papers examine the effects on health and education levels influence the level of public understanding about the dangers to public health food formalin. This study uses the population of the village community in RW.04 Kronjo of RT.01 and 02 by using a random sample technique. Data collection using the enclosed questionnaire and interview instruments. The results showed that (1) The education level of respondents about (40%) graduated from junior high school, (2) Almost all respondents aware of any food formalin (87.27%), (3) About (36.36%) of respondents felt uneasy in the presence of food formalin, (21.09%) know the negative effects of formaldehyde, (4) almost all respondents (85.45%) know that formaldehyde is not a food preservative, (5) almost all the people (72.73%) did not know how to remove formalin of foodstuffs. The conclusion of this study is the lack of education and public understanding that the community does not know how to respond to the food formalin. Key words: Education, Understanding, Health, Formalin.